Weight change among people randomized to minimal intervention control groups in weight loss trials. Issue 4 (April 2016) - Johns, David J.; Hartmann‐Boyce, Jamie; Jebb, Susan A.; Aveyard, Paul; ,
Abstract : Objective: Evidence on the effectiveness of behavioral weight management programs often comes from uncontrolled program evaluations. These frequently make the assumption that, without intervention, people will gain weight. The aim of this study was to use data from minimal intervention control groups in randomized controlled trials to examine the evidence for this assumption and the effect of frequency of weighing on weight change. Methods: Data were extracted from minimal intervention control arms in a systematic review of multicomponent behavioral weight management programs. Two reviewers classified control arms into three categories based on intensity of minimal intervention and calculated 12‐month mean weight change using baseline observation carried forward. Meta‐regression was conducted in STATA v12. Results: Thirty studies met the inclusion criteria, twenty‐nine of which had usable data, representing 5, 963 participants allocated to control arms. Control arms were categorized according to intensity, as offering leaflets only, a single session of advice, or more than one session of advice from someone without specialist skills in supporting weight loss. Mean weight change at 12 months across all categories was −0.8 kg (95% CI −1.1 to −0.4). In an unadjusted model, increasing intensity by moving up a category was associated with an additional weight loss of −0.53 kg (95% CI −0.96 to −0.09). Also in an unadjusted model, each additional weigh‐in was associated with a weight change of −0.42 kg (95% CI −0.81 to −0.03). However, when both variables were placed in the same model, neither intervention category nor number of weigh‐ins was associated with weight change. Conclusions: Uncontrolled evaluations of weight loss programs should assume that, in the absence of intervention, their population would weigh up to a kilogram on average less than baseline at the end of the first year of follow‐up.